Understanding public knowledge and awareness on e-waste in an urban setting in India: A case study for Delhi. Issue 6 (2nd September 2014) - Kwatra, Swati; Pandey, Suneel; Sharma, Sumit
Abstract : Purpose: – Despite legislation in place, there is still a gap in knowledge and awareness of the communities on the issues of e-waste handling and management. It is important to understand the knowledge and awareness levels of the consumers of electronic products who ultimately become the generators of e-waste in a community. The current study is based on a survey conducted in an urban setting to understand people's perception about the genesis of issues related to e-waste and its management. The purpose of this paper is to study the findings that could help in designing customized awareness programmes for addressing this concern more effectively. Design/methodology/approach: – A survey was conducted in Delhi to understand public knowledge and awareness related to e-waste management in the city and country. A limited random survey was conducted with a sample size of 400 individuals in Delhi from middle class belonging to different educational backgrounds and professions. Personal interview method was used to collect in-depth information related to the issues of e-waste and its management. A questionnaire was developed and pilot tested before actual start of the survey. The questionnaire consisted of two sections – first about baseline information related to their age, family size, family income and educational background and second on their knowledge and awareness regarding e-waste and its management. Also, the practices they followed regarding e-waste at their household level were enquired. The questionnaire consisted of both open-ended and close-ended questions. Most of the questions had multiple-choice options, which made it easy for the respondents to answer them appropriately. The open-ended question gave the respondents ample time and space to express their views. The open-ended questions besides strengthening the close-ended questions provided a lot of qualitative information and made the study interesting. Apart from just interviewing, informal interactions were also used as a tool for data collection. During the course of the study, informal interactions were done with respondents to familiarize them with the objectives of the present study, their role and benefits to them from the study. Findings: – The present study aimed to gauge the awareness levels and practices of people regarding e-waste management. The survey conducted in Delhi revealed that significant fraction of middle-class population is still unaware of the issue; however, on getting the information they were able to link the impacts of improper management of e-waste with detrimental health outcomes. For those who knew about it, the main sources of information to them were found to be internet, and print media. However, despite some awareness about the issue, most respondents were totally unaware about correct ways of its recycling and management. An important finding of the study was that 12-26 per cent people replace their major electronic goods like refrigerators, food processors, personal computers and music systems within the first three years of purchase. Discarding products within their periods of useful lives leads to enhanced generation of e-wastes. Along with e-waste generation, this also puts additional stress over the resources used for manufacturing of these products. On management of e-waste, most of the respondents opined of need of having efficient recycling units and effective mass awareness programmes. The survey also revealed the willingness of users to pay extra cost for proper management of e-waste provided that there is proper cost sharing between consumers and producers. This also raises an important aspect of extended producer responsibility (EPR). EPR puts additional responsibility and onus on the manufacturer of the product to not only produce durable quality of products but also take back the obsolete products and manage the e-waste. This also means that the manufacturers will have to use recyclable material in manufacturing of new products for economic management of e-waste at the later stage. Although, in Indian context it would be a challenge to implement the concept of EPR, especially with the active informal sector. The respondents quite adequately put equal responsibilities on the government, consumers and producers for effective e-waste management. The study clearly highlights the issues perceived by the middle-class population of Delhi and can be replicated in other major cities for re-authentication of the facts. The study could prove to be important in designing awareness programme related to the issue. Originality/value: – This paper presents the results of a questionnaire survey-based study that was employed to understand the perception of a sample of respondents. Analysis of the data reveals that the knowledge on the issue of e-waste is minimal and requires massive awareness drives for senitization.